2011
DOI: 10.1208/s12249-011-9707-x
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Drugs in Aqueous Polymeric Solution: Effect of Ovalbumin on Microencapsulation Process

Abstract: Abstract. Microencapsulation of water-soluble drugs using coacervation-phase separation method is very challenging, as these drugs partitioned into the aqueous polymeric solution, resulting in poor drug entrapment. For evaluating the effect of ovalbumin on the microencapsulation of drugs with different solubility, pseudoephedrine HCl, verapamil HCl, propranolol HCl, paracetamol, and curcuminoid were used. In addition, drug mixtures comprising of paracetamol and pseudoephedrine HCl were also studied. The morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Owing to increased surface area of the produced nanocrystals, a significant difference (P<0.001) was observed in solubility of the processed ARM compared to the solubility in water and stabilizer solution. There has been previously reported that water soluble polymers and surfactants (HPMC, PVP and SLS) can increase solubility of drug compounds (Aziz, et al, 2012;Leuner and Dressman, 2000). We also observed an increase in solubility of ARM in stabilizer solution (PVA).…”
Section: Solubility Studiessupporting
confidence: 73%
“…Owing to increased surface area of the produced nanocrystals, a significant difference (P<0.001) was observed in solubility of the processed ARM compared to the solubility in water and stabilizer solution. There has been previously reported that water soluble polymers and surfactants (HPMC, PVP and SLS) can increase solubility of drug compounds (Aziz, et al, 2012;Leuner and Dressman, 2000). We also observed an increase in solubility of ARM in stabilizer solution (PVA).…”
Section: Solubility Studiessupporting
confidence: 73%
“…Despite water-soluble polymers and surfactants such as HPMC, PVP, and SLS being well known to increase the solubility of drug compounds,67,68 the comparison of the solubility profile of the nanosuspension with that of the unprocessed ARTM dissolved in these same surfactants clearly demonstrates that the nanocrystals provide a substantially increased saturation solubility of ARTM. This phenomenon we believe is ascribed to the marked reduction in particle size (=1,000 nm) and the greatly increased surface area of the particles.…”
Section: Resultsmentioning
confidence: 99%
“…For oral drug delivery, improvement of drug solubility is the main challenge in drug formulations process (Khadka et al, 2014 ). Many approaches had been investigated and applied either alone or in combination for improving the solubility characteristics of poorly water soluble drugs including solvent change co-precipitation (Sertsou et al, 2002 , Khanfar & Salem, 2010 ), solid dispersion (Hosny et al, 2013 ; Maruthapillai et al, 2015 ; Pereira et al, 2016 ), inclusion complexes with β-cyclodextrins (Gao et al, 2012 ; Sambasevam et al, 2013 ; Nair et al, 2014 ), nanosuspensions (Huang et al, 2013 ; Sahu & Das, 2014 ; Gora et al, 2016 ), microencapsulation (Aziz et al, 2012 ), soluble salts formation (Serajuddin, 2007 ), lyophilization (Dixit et al, 2011 ; Dixit & Kulkarni, 2012 ; Xu et al, 2016 ), solubilization (Rangel-Yagui et al, 2005 ; Seedher & Kanojia, 2008 ; Xu et al, 2012 ), and liquisolid technique (Khames, 2013 ; Kamble et al, 2014 ; Sanka et al, 2014 ; Badawy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%